Lugol’s Iodine-Enhanced Micro-CT: A Potential 3-D Imaging Method for Detecting Tongue Squamous Cell Carcinoma Specimens in Surgery - Xia, Cheng-Wan; Gan, Rong-lin; Pan, Jiong-ru; Hu, Shi-qi; Zhou, Qun-zhi; Chen, Shen; Zhang, Lei; Hu, Qin-Gang; Wang, Yu-Xin (Frontiers in Oncology, 2020)
Background: A positive surgical margin (PSM) following oral cancer resection results in local recurrence and poor prognosis. Mono-block tumor specimens are difficult to evaluate, especially at the tumor base. This inaccurate sampling ultimately leads to false pathological diagnosis. Lugol's iodine (I 2 -IK)-enhanced micro-CT is an emerging method to image tumor specimens. This study explored the feasibility of I 2 -IK-enhanced micro-CT to evaluate the surgical margin for tongue squamous cell carcinoma (TSCC) specimens, and to further seek the optimal staining parameters.Rabbit tongue tissues and human TSCC samples were imaged via I 2 -IK-enhanced micro-CT. The optimal I 2 -IK concentration and staining time were determined before clinical application with tissue shrinkage, micro-CT image quality, and effect on pathological diagnosis as assessment criteria. Next, 6 TSCC specimens were used to verify the feasibility for surgical margin imaging with the optimal parameters. Finally, the possible reason by which I 2 -IK could enhance micro-CT imaging was validated in vitro.Results: I 2 -IK staining influenced specimen shrinkage, micro-CT image quality, and pathological image quality in a concentration/time-dependent manner. After comprehensively considering the indicators, 3% I 2 -IK staining for 48 h and for 12 h was optimal for rabbit tongue tissues and TSCC samples, respectively. This method could provide a detailed and 3D structure of TSCC samples compared with H&E sections. Moreover, tumor and normal tissues may be differentiated by the content of glycogen, which has high affinity with I 2 -IK.Conclusions: I 2 -IK-enhanced micro-CT could thus indicate the tumor margin and assist pathological sampling for patients with TSCC post-operation.